Design, Synthesis, and Evaluation of 1-Benzylpiperidine and 1-Benzoylpiperidine Derivatives as Dual-Target Inhibitors of Acetylcholinesterase and Serotonin Transporter for Alzheimer′S Disease † - Reyes-Parada, M (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Cholinergic neuron impairment is a significant cause of cognitive decline in Alzheimer’s disease (AD), making acetylcholinesterase (AChE) a key therapeutic target. AChE inhibitors are principal drugs prescribed to alleviate symptoms in AD patients, while up to 50% of these individuals also suffer from depression, frequently treated with selective serotonin reuptake inhibitors (SSRIs). Due to the multisymptomatic nature of AD, there is a growing interest in developing multitargeted ligands that simultaneously enhance cholinergic and serotonergic tone. This study presents the synthesis of novel ligands based on functionalized piperidines, evaluated through radioligand binding assays at the serotonin transporter (SERT) and AChE and butyrylcholinesterase (BuChE) inhibition. The pharmacological results showed that some compounds exhibited moderate inhibitory activity against AChE, with one compound 19 standing out as the most potent, also displaying a moderate BuChE inhibitory activity, while showing low affinity for SERT. On the other hand, compound 21 displayed an interesting polypharmacological profile, with good and selective activity against BuChE and SERT. The results underscore the difficulty of designing promiscuous ligands for these targets and suggest that future structural modifications could optimize their therapeutic potential in AD. © 2025 by the authors.